ANTIOXIDANT AND ANTI-FATIGUE ACTIVITIES OF FLAVONOIDS FROM PUERARIAE RADIX - Xiaoming, Wang; Ling, Lei; Jinghang, Zhang (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
This study evaluated the antioxidant and anti-fatigue activities of flavonoids from Puerariae radix (FPR). In vitro antioxidant activities of FPR were investigated through hydroxyl and superoxide radical scavenging activities. In vivo anti-fatigue activity of FPR was investigated through loaded swimming exercise of mice. Results showed that FPR had not only in vitro antioxidant activities, but also an in vivo anti-fatigue activity in mice. FPR possessed superoxide and hydroxyl radical scavenging activity in in vitro experimental studies. In vivo experimental studies, FPR could evidently extend exhaustive swimming time of mice, inhibit the increase of blood lactic acid (BLA), decrease serum urea nitrogen (BUN) and malondialdehyde (MDA) contents, promote increases in the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPX) of mice after swimming. The results provided an important basis for developing the FPR as a novel antioxidant and anti-fatigue compound.